Thermochemical behavior of perovskite oxides based on LaxSr1-x(Mn, Fe, Co)O3-δ and BaySr1-yCoO3-δ redox system for thermochemical energy storage at high temperatures. (15th March 2019) - Gokon, Nobuyuki; Yawata, Takehiro; Bellan, Selvan; Kodama, Tatsuya; Cho, Hyun-Seok
Abstract: Lax Sr1-x (Mn, Fe, Co)O3-δ, and Bay Sr1-y CoO3-δ perovskite oxide powders were investigated as potential thermochemical energy storage (TES) materials operated at high temperatures above 600 °C. The purpose of the research is to provide complete characterization of the impact of partial A- and B-site substitution on the reactivity, kinetics, redox reaction repeatability and charging/discharging storage capacity. The perovskite oxides were investigated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) at temperatures of 500–1100 °C. Thermal energy storage was evaluated in terms of the enthalpy of the reversible reactions of oxygen release (reduction) and uptake (oxidation) upon heating the oxide materials in air stream. Among the perovskites tested, Ba0.3 Sr0.7 CoO3-δ and Ba0.7 Sr0.3 CoO3-δ powders were suitable thermochemical storage materials operating at above 600 °C in terms of chemical reactivity, charging/discharging temperatures and storage capacities, kinetics of oxygen uptake/release, and repeatability of thermochemical cycling. Further, charging/discharging capacity for both perovskites was comparable to that for Fe-doped manganese oxide. Highlights: Perovskite oxides were examined as a TES operating at temperatures above 600 °C. B site of LaSr series oxides exhibited a pronounced influence on the reactivities. Oxygen uptake kinetics of BaSr series increase with increasing Ba content. BS73C and BS37C showed hysteresis loops of 700–920 °C and 600–950 °C, respectively. BS37C and BS73C were comparable to Fe-doped Mn2 O3 for thermochemical capacity.